Trend in the Utilization of Antipsychotics in the National Health Coverage Era in Indonesia: A Cross-Sectional Study - Julaeha, Julaeha; Yuliana, Verra; Ayuningtyas, Josephine Paramita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The utilization pattern of antipsychotics has undergone significant changes since the introduction of atypical antipsychotics. Currently, medication for patients with schizophrenia predominantly uses atypical antipsychotics rather than typical antipsychotics. This study aimed to present the updated utilization pattern of antipsychotics among Indonesians. A cross-sectional study was conducted in 2019-2020 at the National Mental Hospital in Indonesia. Data were collected from medication-used reports from either inpatients or outpatients. A descriptive analysis was conducted to present the pattern and the annual total cost for each antipsychotic used. The pattern of typical antipsychotics used from 2019 to 2020 was likely to decline. The total cost estimated for typical antipsychotics in 2019 was IDR 475 million, and IDR 420 million in 2020. Trifluoperazine 5 mg was the most commonly typical antipsychotic used, followed by chlorpromazine 100 mg and haloperidol 5 mg. Eventually, the pattern of atypical antipsychotics used was likely to increase. The total cost was estimated at IDR 3.2 billion in 2019 and IDR 3.8 billion in 2020. Risperidone 2 mg was the most commonly atypical antipsychotic used, followed by clozapine 25 mg and risperidone 3 mg. This study proves the trend toward increased atypical antipsychotics used. Accordingly, the cost of schizophrenia treatment was elevated.